Clinical Profile and Risk Factors of Urinary Tract Infection in Diabetic and Non-Diabetic Patients: A Comparative Study - V. Saranya; K. Suresh (The Bioscan, 2025)
Background: Urinary tract infection (UTI) is the most common infections in diabetic individuals. Due to immunosuppression and glycosuria, diabetic patients are predisposed to recurrent and complicated UTIs. Aim: To evaluate and compare the clinical profile, symptom severity, and risk factors of UTI in diabetic and non-diabetic patients. Methods: This prospective cross-sectional study was conducted over 18 months at a tertiary care hospital in Puducherry. A total of 126 patients presenting with symptoms of UTI were recruited and classified into diabetic and non-diabetic groups. Clinical symptoms, demographic data, and predisposing risk factors were recorded. Statistical analysis was done to identify significant associations. Results: The mean age was 46.99 ± 11.70 years; 65.9% were females. Dysuria (p<0.001), abdominal pain (p<0.001), vomiting (p=0.005), hematuria (p=0.011), pyuria (p=0.017), incontinence (p<0.001), retention (p=0.002), and pyelonephritis (p=0.008) were significantly more frequent in diabetic patients. There was a strong association between diabetic status and lower SES, BMI, and occupation. However, no individual anatomical or catheter-related factor showed a significant correlation with diabetes status. Escherichia coli were the most common organism across both groups. Conclusion: Diabetic patients presented with more severe symptoms and higher complication rates. Routine UTI screening and aggressive management in diabetic patients are vital to prevent morbidity.